Effect of Osteopontin Alleles on β-Glucan-Induced Granuloma Formation in the Mouse Liver - Tanaka, Kumiko (American Society for Investigative Pathology, 2004)
The granuloma formation is a host defense response against persistent irritants. Osteopontin is centrally involved in the formation of granulomas. Three osteopontin alleles, designated a, b, and c, have been found in mice. Here we used a murine model of zymosan (β-glucan)-induced granuloma formation in the liver to determine possible functional differences between the osteopontin alleles in cell-mediated immunity. In contrast to mice with alleles a or c, mice with the allele b was defective in granuloma formation. As detected by mRNA expression, cytokines and chemokines known to be critically involved in granuloma formation were elicited in liver tissue, regardless of the osteopontin allele expressed. Alignment of the deduced amino acid sequences showed that unlike osteopontin c, b differs from a in 11 amino acids. All three osteopontin alleles had normal cell-binding properties. However, only the b allelic form was defective in the induction of cell migration as tested with dendritic cells. In conclusion, generation of a granulomatous response in mice depends critically on the presence of a functional osteopontin allele. Defective granuloma formation in mice with allele b is likely to be because of an impaired chemotactic function of the osteopontin b protein on immunocompetent cells.